The profile of Hip and Knee Periprosthetic Joint Infection cases at Dr. Cipto Mangunkusumo Central National Referral Hospital - Eko Prasetyo Adi Wibowo; Ismail Hadisoebroto Dilogo (The Hip and Knee Journal, 2021)
Background: The most troubling complication of joint replacement procedures is periprosthetic joint infection (PJI). Pathogen identification increases the likelihood of successful treatment. The data of PJI are mostly unpublished in Indonesia. In this study we aimed to investigate the characteristics of PJI of a national hospital in Indonesia. Material and methods: This research was a cross-sectional study. The inclusion criteria were patients diagnosed with PJI confirmed by examination of fluid exudate culture, sedimentation rate and C-Reactive Protein, which was accompanied by dislocation, fracture and/or loosening of the prosthetic joint and diagnosed between January 2019 to July 2020. Result: The mean age of patients who underwent revision surgery for PJI was 50.0 ± 14.69 years-old with a slightly higher proportion of men (63.6%). Of the 21 patients, some patients had a history of surgery more than once. The clinical outcome was assessed with the Harris Hip Score (HHS) and the Visual Analog Scale (VAS). The mean HHS of all hip replacement surgeries increased from 61.4 (48.15 to 68) before surgery to 82.5 (75.7 to 84) at the 12-month follow-up post last surgery (p=0.03). Likewise, the VAS value decreased from 3 (2 to 4) before surgery to 2 (1 to 2). Conclusion: Gram positive bacteria were more prevalent compared to gram negative bacteria. The difference in the microorganism spectrum could be one of several factors. This pattern should be explored in the future by adding more samples to the study. Overall, the clinical outcome was better in both total hip and knee arthroplasty patients, measured by the Harris hip score, visual analog scale, and the knee society score